L'engagement des étudiants dans les forums de discussion des MOOC : dimensions et indicateurs - Yannick Stéphane Nleme Ze; Gaëlle Molinari (Centre National d'Enseignement à Distance, 2021)
This paper aims to clarify the notion of engagement in MOOCs discussion forums as perceived by students. To do this, we relied on the qualitative approach used by Fredricks et al. (2016) in the context of mathematics and science. The analysis of the eleven semi-structured interviews conducted with MOOCs students highlights three main findings. First, engagement as a construct with four dimensions (behavioural, affective, cognitive and social). Secondly, a clear distinction between these dimensions using the related indicators we have identified. Finally, the dynamic aspect of engagement: engagement may be absent, low or high among students. These results provide a socially and contextually grounded definition of engagement in MOOCs forums that ensures the development of reliable and essential tools for measuring it and observing its quality over time.